Intestinal inflammation in TNBS sensitized rats as a model of chronic inflammatory bowel disease - N. Selve; T. Wöhrmann (Mediators of Inflammation)
An enteritis, based on a delayed-type hypersensitivity reaction, was induced in TNBS (2,4,4-trinitrobenzenesulphonic acid) sensitized rats by multiple intrajejunal challenge with TNBS via an implanted catheter. This treatment induced chronic inflammation of the distal small intestine characterized by intense hyperaemia, oedema and gut wall thickening as assessed by macroscopic scoring and weighing a defined part of the dissected intestine. Histologically, the inflammatory response included mucosal and submucosal cell infiltration by lymphocytes and histiocytes, transmural granulomatous inflammation with multinucleated cells and activated mesenteric lymph nodes. Ex vivo stimulated release of the inflammatory mediator LTB4 in the dissected part of the intestine was increased following TNBS treatment. Drug treatment with sulphasalazine or 5-aminosalicylic acid improved the enteritis score and attenuated TNBS induced oedema formation and LTB4 production. The applicability and relevance of this new model are discussed with respect to drug development and basic research of inflammatory bowel diseases.